2011
DOI: 10.1242/dev.063966
|View full text |Cite
|
Sign up to set email alerts
|

SHH propagates distal limb bud development by enhancing CYP26B1-mediated retinoic acid clearance via AER-FGF signalling

Abstract: SUMMARYThe essential roles of SHH in anteroposterior (AP) and AER-FGF signalling in proximodistal (PD) limb bud development are well understood. In addition, these morphoregulatory signals are key components of the self-regulatory SHH/GREM1/AER-FGF feedback signalling system that regulates distal progression of limb bud development. This study uncovers an additional signalling module required for coordinated progression of limb bud axis development. Transcriptome analysis using Shh-deficient mouse limb buds re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 55 publications
6
115
0
Order By: Relevance
“…We cannot, however, exclude another possible explanation of the incomplete rescue: that Meis genes affect Hoxa13 expression via multiple parallel pathways, RA being only one of them. Notably, the fact that the MEIS effect is cell-autonomous, despite acting through a diffusible signal (RA) is consistent with studies showing that RA degradation by CYP26 enzymes has a more determining role than RA diffusion on tissue patterning, very likely due to the different kinetics of the two processes (Hernandez et al, 2007;Probst et al, 2011;White et al, 2007).…”
Section: Meis Genes Control Spatial Distribution Of Hoxa13 Expressionsupporting
confidence: 80%
See 2 more Smart Citations
“…We cannot, however, exclude another possible explanation of the incomplete rescue: that Meis genes affect Hoxa13 expression via multiple parallel pathways, RA being only one of them. Notably, the fact that the MEIS effect is cell-autonomous, despite acting through a diffusible signal (RA) is consistent with studies showing that RA degradation by CYP26 enzymes has a more determining role than RA diffusion on tissue patterning, very likely due to the different kinetics of the two processes (Hernandez et al, 2007;Probst et al, 2011;White et al, 2007).…”
Section: Meis Genes Control Spatial Distribution Of Hoxa13 Expressionsupporting
confidence: 80%
“…3A, n=0/6). To discard the possibility that additional signals were needed, we also applied beads soaked in the distal signals FGF8 and sonic hedgehog (SHH) (Mariani et al, 2008;Mercader et al, 2000;Probst et al, 2011), but this was again insufficient to prematurely activate Hoxa13 expression at 10 hpi (Fig. 3C,n=0/8).…”
Section: Time Is Also Necessary For Hoxa13 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…This regulation could reflect direct trans-activation by HOX proteins and/or indirect regulation through intermediary molecules. Supporting a contribution from the latter scenario, it was reported that Shh, which is activated by Hox function (Kmita et al 2005), is required for normal Shox2 transcript levels at E10.5 (Probst et al 2011). This downregulation of Shox2 expression is transient, however, as HoxA c/c ; HoxD 2/2 animals show similar Shox2 expression at E11 to wild type, despite having a drastic difference in limb bud morphology ( Figure 5).…”
Section: Resultsmentioning
confidence: 63%
“…Since signaling circuitry involving the AER and underlying mesenchyme has been reported to be inhibited by high levels of RA, which is thought to mimic an exaggerated version of proximal signals (Probst et al, 2011), we investigated whether RING1 activity could be influenced by excess RA signaling. We thus examined whether transient increases in RA signaling at E10.5 could modify the limb defects in Ring1B mutant mice.…”
Section: Ring1 Activity Is Correlated With Regionalizing Signals Of Fmentioning
confidence: 99%